Social Connectedness in the Digital Age: Senior Citizens’ Experiences (International Forum Journal, 2020)
Connectedness through face-to-face interactions can be vital for all people. However, senior citizens have a distinct perspective as to what valuable social interaction is. By using the theory of connectedness, this study explored the experiences of senior citizens on social connectedness through face-to-face communication. This phenomenological study utilized the six steps of Van Manen in exploring and analyzing the experiences of the senior citizens. Twelve senior citizens served as participants and were selected through purposive and snowball sampling techniques. The study was conducted in the coastal or lowland barangays of Ozamiz City, Misamis Occidental, Philippines. The analysis of the data revealed five central themes: comfort in physical presence, strength in spirituality, sense of belonging, feeling of relief, and acceptance of old age.
Keywords: connectedness; face-to-face interactions; gerontology; hermeneutic; phenomenology; Ozamiz City; Misamis Occidental; Philippines; senior citizens; social network; Southeast Asia